2017 IEEE Information Theory Workshop (ITW) 2017
DOI: 10.1109/itw.2017.8278006
|View full text |Cite
|
Sign up to set email alerts
|

The multi-layer information bottleneck problem

Abstract: The muti-layer information bottleneck (IB) problem, where information is propagated (or successively refined) from layer to layer, is considered. Based on information forwarded by the preceding layer, each stage of the network is required to preserve a certain level of relevance with regards to a specific hidden variable, quantified by the mutual information. The hidden variables and the source can be arbitrarily correlated. The optimal trade-off between rates of relevance and compression (or complexity) is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The bound I(f (X n ); g(Y n )) ≤ I(X; Y) was established, which is tight if and only if f and g are dictator functions. There are many other variations of multi-user IB in the literature [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…The bound I(f (X n ); g(Y n )) ≤ I(X; Y) was established, which is tight if and only if f and g are dictator functions. There are many other variations of multi-user IB in the literature [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Seq2Seq models are also used extensively for the dynamic, spatial-temporal characteristic of multivariate time series data (Zhu and Laptev, 2017 ; Du et al, 2018 ; Yang et al, 2019 ; Salinas et al, 2020 ). Another application of the sequence to sequence model is in video and image captioning (Venugopalan et al, 2015 ; Yang et al, 2017 ).…”
Section: Time Series Prediction Methods For Mitigating Time Delay mentioning
confidence: 99%
“…Since then, it was applied to derive several clustering algorithms for a wide variety of applications such as: text classification [8], galaxy spectra classification [9], speaker recognition [10], among others. Further information-theoretic extensions of the IB were recently considered in [11]- [15]. In particular, in some of these works it is shown that the same characterization of the rate and distortion tradeoff is obtained when the distortion metric is not necessarily additive as assumed in (2).…”
Section: A Related Workmentioning
confidence: 99%